Diagnostic Value of Fine Needle Aspiration Cytology in the Diagnosis of Solitary Thyroid Nodule (Medical Forum Monthly, 2024)
Objectives:- To evaluate usefulness of the FNAC in diagnosing solitary thyroid nodule.Study Design: Interventional studyPlace and Duration of Study: This study was carried out in the Department of General Surgery, Nishtar Medical College, Multan from January 2010 to July 2010.Material and methods:- A total of 100 patients were included in the study.Results:- Majority of the patients i.e. 40 (66.7%) patients were between the 21-40 years. Of the 60 patients, 10 (16.7%) patients were male while 50 (83.3%) patients were female. Thirty five (58.3%) patients belonged to district Multan while 10 (16.7%) patients were residents of district Muzaffargarh. Mild pain was noted in 6 (10%) patients 3 (5%) patients had change in voice and 3 (5%) patients had palpitation. Thirty patients (50%) presented within one year of the start of their disease. Right lobe of the thyroid gland harboured swelling in 45 patients (75%). Only 3 patients (5%) were diagnosed as papillary carcinoma. Conclusion:- Cold thyroid nodule is a common problem and has gained much significance due to its potential for malignancy.